Prevalence of hematuria and proteinuria in asymptomatic pediatric age group in suburban Chennai - Belukurichi Sadasivam Sangeetha,; Rajesh Haridass,; Jamunarani Srirangaramasamy,; Chinnadurai Peermohamed Luck,; Sumithasree Ramamoorthi, (Asian Journal of Medical Sciences, 2023)
Background: Hematuria is rare in normal physiology. Proteinuria is almost always abnormal. It has been reported that hematuria and proteinuria are present even in apparently healthy children. Aims and Objectives: This study was carried out to find the prevalence of proteinuria and hematuria in asymptomatic pediatric age group in suburban Chennai. Materials and Methods: This cross-sectional study was carried out among 200 apparently healthy children of a suburban community in Chennai. Urine samples were collected from all children who satisfied the study criteria. The study period was from June 2020 to December 2021. The collected urine samples were analyzed in the laboratory for hematuria and proteinuria. The data were entered into Microsoft Excel and analyzed using SPSS version 23. Results: Of the 200 children, 105 (52.5%) were males and 95 (47.5%) were females. The mean±standard deviation of the age of the study participants was 6.275±4.0362. Twenty-nine (14.5%) had hematuria, 45 (22.5%) had proteinuria, and 10 (5%) children had both. Conclusion: Hematuria and proteinuria are present in asymptomatic children. Urinalysis is an effective, easy, and non-invasive screening method for early detection of an underlying renal disease.